Ultrasound Evaluation of Primary Alveolar Grafting in Cleft Lip/Palate Treatment: Development of a Novel Sonographic Grading System. (September 2016) - Chang, Daniel K.; Kanack, Melissa; Pretorius, Dolores; Calvert, Stephanie; Patino-Ochoa, Cesar; Gosman, Amanda
Objective: To explore ultrasonographic evaluation of primary alveolar repair in cleft lip/palate patients and develop a grading system to assess outcomes of graft success. Design: Sixteen patients with an average age of 2 years 1 month had sonograms performed at various points in their treatment to determine the feasibility of ultrasound in visualizing alveolar bone defects and changes over time postgrafting. A total of 23 sonograms were performed: 21 at an average of 12 months postoperatively and 2 at an average of 1 month preoperatively. Main Outcome Measures: A 10-point grading system was developed assessing three categories: locations of lateral bone bridging across the cleft, quantification of residual defects with air or fluid channels, and locations of calcification. Three operators graded 10 sonograms to assess interobserver reliability, and the scores were also validated against dental radiographs in patients old enough for radiographic imaging. Results: Linear weighted kappa statistics revealed substantial interobserver agreement for total scores, with an average kappa value of .708. In limited patients with radiographs, a total score of 9/10 correlated with a Chelsea score of 6.5/8 and category A. Conclusions: Sonographic evaluation, coupled with this novel grading system, shows potential for early assessment of outcomes of graft success when evaluating new techniques of primary alveolar grafting.